Seasonal affective disorder and light therapy [MEVSIMSEL DUYGULANIM BOZUKLUGU VE ISIK TEDAVISI] - (:unkn) unknown (My University, 1995)
Seasonal affective disorder (SAD) is a subgroup of the affective disorders. This syndrome is characterized by recurrent depressions that occur annually at the same time each year and appears as a result of the reactivity of the patients to changes in some environmental factors like climate, latitude, or light. Light therapy is an effective treatment for SAD. In this paper the clinical features, epidemiology, light therapy and pathophysiology of SAD is reviewed in the light of the literature.
Keywords: Light therapy; Seasonal effective disorder